1983
DOI: 10.3102/00346543053004499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activity-based Elementary Science on Student Outcomes: A Quantitative Synthesis

Abstract: In this study, meta-analysis techniques were used to synthesize research on the effectiveness of three major activity-based elementary science programs (ESS, SAPA, and SCIS), which were developed with federal support. In 57 controlled studies, outcomes were measured in over 900 classrooms; the overall mean effect size for all outcome areas was .35. The mean effect size was .52 for science process tests, .16 for science content, and .28 for affective outcomes. On the average, gains also were realized in creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
5

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(56 citation statements)
references
References 42 publications
(15 reference statements)
5
46
0
5
Order By: Relevance
“…What is noteworthy is that no interaction between time and achievement level could be detected; in other words, the lower achieving students benefited from the intervention as much as average and high achieving students. Bredderman (1983) reviewed the results of three ''activity-based'' science programmes designed for elementary students. The conclusion was that positive results could be detected mainly in terms of ''inquiry skills''.…”
Section: Previous Studies On the Impact Of Project-based Learning Andmentioning
confidence: 99%
“…What is noteworthy is that no interaction between time and achievement level could be detected; in other words, the lower achieving students benefited from the intervention as much as average and high achieving students. Bredderman (1983) reviewed the results of three ''activity-based'' science programmes designed for elementary students. The conclusion was that positive results could be detected mainly in terms of ''inquiry skills''.…”
Section: Previous Studies On the Impact Of Project-based Learning Andmentioning
confidence: 99%
“…In 1977, 65% of K-3 classes and 54% of 4-6 classes had used a hands-on activity of some type in their most recent lesson, by 1985-1986 these percentages had dropped to 57% for K-3 classes and 45% for 4-6 classes (Weiss, 1987). Currently, 38% of elementary science classes are taught in rooms with no science facilities or materials (Weiss, 1987) even though research has shown that investigative, inquiry-oriented and/or process approach science activities can actually help improve children's performance even in traditional science classes (Bredderman, 1983;Kyle, Shymansky, & Alport, 1982;Shymansky, Kyle, & Alport, 1982a, 1982b.…”
mentioning
confidence: 99%
“…Inquiry science teachers "focus and support inquiries while interacting with students," "orchestrate discourse among students about scientific ideas," "challenge students to accept and share responsibility for their own learning," "recognize and respond to student diversity and encourage all students to participate fully in science learning," and "encourage and model the skills of scientific inquiry, as well as the curiosity, openness to new ideas and data, and skepticism that characterize science" (NRC, 1996, p. 32). A number of studies and metaanalyses (Bredderman, 1983;Cohen & Spillane, 1993;Lee, Hart, Cuevas & Enders, 2004;Lott, 1983;NRC, 1996;Shymansky, Kyle & Alport, 1983;Tamir, 1983;Von Secker & Lissitz, 1999;Wise & Okey, 1983;Wu & Hsieh, 2006) have shown that inquiry science has positively affected a variety of student outcomes such as achievement and attitudes, process skills, problem solving and creativity, vocabulary knowledge, conceptual understanding and critical thinking, inquiry abilities, and "scientific ways of thinking, talking, and writing" (NRC, 1996, p. 125; see also Anderson, 2002). 1…”
Section: Inquiry Sciencementioning
confidence: 97%